A Model of the Commercial Loan Rate - SLOVIN, MYRON B.; SUSHKA, MARIE ELIZABETH (Journal of Finance, 1983)
ABSTRACT This paper explores the theoretical and empirical determinants of the commercial loan rate charged by commercial banks based on a model of financial intermediary behavior which assumes monopolistic competition in asset and liability markets. The model incorporates the constraint that banks must maintain at least a minimum quantity of bonds in asset portfolios. Equations are estimated on a time series basis to explain the behavior of commercial loan rates over the period 1953 to 1980. The evidence appears consistent with the hypothesis that commercial banks operate in a market characterized by imperfect competition and that they explicitly set loan rates.